The revolution that wasn't : GameStop, Reddit, and the fleecing of small investors - Jakab, Spencer (Portfolio/Penguin, 2022)
"From Wall Street Journal columnist Spencer Jakab, the real story of the GameStop squeeze-and the surprising winners of a rigged game. During one crazy week in January 2021, a motley crew of retail traders on Reddit's r/wallstreetbets forum had seemingly done the impossible-they had brought some of the biggest, richest players on Wall Street to their knees. Their weapon was GameStop, a failing retailer whose shares briefly became the most-traded security on the planet and the subject of intense media coverage. The Revolution That Wasn't is the riveting story of how the meme stock squeeze unfolded, and of the real architects (and winners) of the GameStop rally. Drawing on his years as a stock analyst at a major bank, Jakab exposes technological and financial innovations such as Robinhood's habit-forming smartphone app as ploys to get our dollars within the larger story of evolving social and economic pressures. The surprising truth? What appeared to be a watershed moment-a revolution that stripped the ultra-powerful hedge funds of their market influence, placing power back in the hands of everyday investors-only tilted the odds further in the house's favor. Online brokerages love to talk about empowerment and "democratizing finance" while profiting from the mistakes and volatility created by novice investors. In this nuanced analysis, Jakab shines a light on the often-misunderstood profit motives and financial mechanisms to show how this so-called revolution is, on balance, a bonanza for Wall Street. But, Jakab argues, there really is a way for ordinary investors to beat the pros: by refusing to play their game."--